Artificial Intelligence Supported Healthy Unit Hybrid Lighting Control - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
In recent years, it has been stated that proper lighting control in hospitals and similar health institutions has positive effects on the patient and working health team. In this study, the intelligent lighting system was designed by using artificial intelligence for examination and observation rooms of a health institution. In this design, natural and artificial lighting hybrid systems are used to provide maximum benefit from natural lighting by using artificial neural networks. According to the results of the analysis, it is concluded that the daylight assisted system has positive effects on both the patients and healthcare workers who use these areas and that energy saving is achieved with high energy efficiency. © 2019 IEEE.
Keywords: artificial neural networks; Hospital lighting; hybrid lighting systems; light shelves